2018
DOI: 10.1186/s12885-018-4439-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the treatment of pancreatic exocrine insufficiency on survival of patients with unresectable pancreatic cancer: a retrospective analysis

Abstract: BackgroundMalnutrition and weight loss are commonly observed in patients with pancreatic cancer and contribute to poor survival. Pancreatic exocrine insufficiency (PEI), which can be caused by ductal obstruction by a tumor, causes maldigestion and malabsorption of nutrients, thus contributing to malnutrition in these patients. In this study, we evaluated the effects of pancreatic enzyme replacement therapy (PERT) on survival in patients with unresectable pancreatic cancer.MethodsA retrospective analysis was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 36 publications
1
79
0
4
Order By: Relevance
“…One retrospective study suggested exocrine pancreatic insufficiency was associated with reduced survival in patients with chronic pancreatitis 39 . A number of cohort studies, 22,40,41 a population‐based cohort study, 26 and some small randomised trials 42,43 have assessed the benefit of PERT in patients with pancreatic cancer. While results are not uniform, the largest population‐based analysis 26 demonstrates significantly improved survival (adjusted survival 2.62‐fold greater than those not on PERT [95% CI 2.27‐3.02]).…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective study suggested exocrine pancreatic insufficiency was associated with reduced survival in patients with chronic pancreatitis 39 . A number of cohort studies, 22,40,41 a population‐based cohort study, 26 and some small randomised trials 42,43 have assessed the benefit of PERT in patients with pancreatic cancer. While results are not uniform, the largest population‐based analysis 26 demonstrates significantly improved survival (adjusted survival 2.62‐fold greater than those not on PERT [95% CI 2.27‐3.02]).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, only patients with good strength can cope with polychemotherapy treatments such as Folfirinox and the gemcitabine-nab-paclitaxel combination. This was shown in a retrospective study of 160 patients with unresectable PC [53]. The authors reported a significantly prolonged survival in patients treated with CT and PERT versus CT alone, and this effect was most pronounced in patients with significant weight loss at diagnosis.…”
Section: Maldigestion and Treatment In Unresectable And Metastatic Pamentioning
confidence: 81%
“…The gold standard, but difficult to perform, three‐day faecal fat test has now largely been replaced by spot faecal elastase assays. In EPI subjects, pancreatic enzyme replacement therapy (PERT) improves steatorrhoea, nutritional parameters, quality of life and mortality 5,6 . Two European observational studies in PC and CP reported under‐utilisation of pancreatic function testing and inadequate PERT dosing 7,8 …”
Section: Chronic Pancreatitis (N = 37 061) Pancreatic Cancer (Nmentioning
confidence: 99%